Life history parameters of the rove beetle Atheta coriaria and efficacy against the fungus gnat Bradysia sp. nr. coprophila - Echegaray, Erik; Cloyd, Raymond A. (My University, 2011)
Fungus gnats (Bradysia spp.) are major pests of greenhouse production systems in the USA. A number of biological control agents have been successfully used in dealing with fungus gnats, including the rove beetle Atheta coriaria, which is a predator that may regulate fungus gnat populations. Despite the evidence associated with its potential as a biological control agent there is no quantitative information available on efficacy of A. coriaria against the fungus gnat Bradysia sp. nr. coprophila. The overall objective of this study was to determine if A. coriaria is a viable biological control agent against fungus gnats under laboratory conditions. Life history parameters were evaluated based on visual observations: Total development time from egg to adult was 15.8 ± 0.39 days at 26°C. After one generation, 69.1 adults were obtained per female; the lowest number of adults per female was 39 while the highest number was 104. Female adult longevity was 47.8 days and the sex ratio was 1:1. A growing medium moisture content <60% may negatively influece adult survival. Efficacy against fungus gnat larvae was evaluated in petri dishes and deli squat containers using growing medium as a substrate, and different predator and prey densities. Although there were no significant differences in prey consumption among the different predator:prey ratios, there was a positive numerical response with higher consumption rates per adult observed at higher prey densities. Consumption rate was higher for second instar than third instar fungus gnat larvae.
Keywords: Biological control; Pest management; Density; Life cycle